Generativity and propensity to teach in Chilean rural educators: educational knowledge from the narrative-generative perspective - Sandoval Obando, Eduardo Enrique; Calvo Muñoz, Carlos Manuel (Innovaciones Educativas, 2022)
The life stories of rural teachers are a relevant historical and cultural tool to reveal those practices and criteria of potentially generative pedagogical action deployed inside and outside the rural school institution. Our objective sought to interpret and understand, from the generative narrative perspective, the behavior patterns built by Chilean rural teachers, which contribute to the systematization of new possibilities for understanding rural teaching professionalism. A qualitative interpretive approach is adopted from the methodological point of view, following a descriptive, exploratory, and transversal design. This sample is intentional and consists of 12 educators with an average of thirty-three years of teaching experience in rural schools in the Metropolitan, La Araucanía, and Los Ríos regions (Chile). For data collection, in-depth interviews were used from the generative narrative perspective. Accordingly, the stories were subjected to content analysis, following the logic of the grounded theory. The main results show that the teaching staff exhibits potentially generative pedagogical action practices and criteria characterized by their commitment to educational work, positive affect, and flexibility, allowing them to build positive and reciprocal interpersonal relationships with the students. In the same way, the propensity to teach that guides their professional work favors the construction of relevant educational learning and historical-sociocultural relevance for students and their communities of origin.